Integration of Neuroleadership and Ottawa Model of Implementation Leadership (O-Mile) in Shaping Millennial Generation Leadership Development - Widiawati, Ira (Journal Research of Social Science, Economics, and Management, 2025)
Millennials now constitute over half of the global workforce, creating pressing demands for leadership approaches that can adapt to rapidly changing organizational environments in the public, healthcare, and education sectors. This study aims to systematically review and integrate two complementary leadership frameworksNeuroleadership, which enhances cognitive–affective skills such as emotional regulation, empathy, and evidence-based decision-making, and the Ottawa Model of Implementation Leadership (O-MILe), which emphasizes task orientation, change management, and relational support to inform millennial leadership development. Using the PRISMA 2020 guidelines, comprehensive searches across Scopus, Web of Science, ProQuest, and SAGE databases identified 247 studies, with 20 meeting the inclusion criteria after quality appraisal using CASP and MMAT tools. Findings reveal that Neuroleadership is primarily applied in corporate contexts to improve self-regulation and strategic decision-making, whereas O-MILe is more prevalent in healthcare and educational settings to facilitate effective change implementation and team support. This review fills a gap in the literature by providing the first integrative analysis of these frameworks for developing adaptive, empathetic, and implementation-focused leadership in millennials. The implications for practice include designing leadership training modules, competency frameworks, and coaching programs that enhance both adaptability and implementation capacity. The integrative approach provides a cross-disciplinary foundation for preparing millennial leaders to address complex organizational challenges, aligning leadership development with the demands of Industry 5.0 and fostering evidence-based, empathetic, and resilient leadership.